2021
DOI: 10.1101/2021.08.03.454861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 B.1.351 (beta) variant shows enhanced infectivity in K18-hACE2 transgenic mice and expanded tropism to wildtype mice compared to B.1 variant

Abstract: SARS-CoV-2 variants display enhanced transmissibility and/or immune evasion and can be generated in humans or animals, like minks, thus generating new reservoirs. The continuous surveillance of animal susceptibility to new variants is necessary to predict pandemic evolution. In this study we demonstrate that, compared to the B.1 SARS-CoV-2 variant, K18-hACE2 transgenic mice challenged with the B.1.351 variant displayed a faster progression of infection. Furthermore, we also report that B.1.351 can establish in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Although there were no significant differences in survival curves and no major clinical signs in the different groups challenged with the Omicron BA.1 variant, viral load was also reduced in lungs from PHH-1V vaccinated animals compared to infected control animals. The reduction of infectivity and pathogenesis of the Omicron BA.1 variant in K18-hACE2 mice has been reported previously in various studies, including a study in which mRNA-1273 protective efficacy was evaluated against Omicron BA.1 (Tarrés-Freixas et al, 2022;Ying et al, 2022). Hence, PHH-1V vaccination can reduce and control infection of different VoCs, including Omicron BA.1, in lower respiratory airways.…”
Section: Discussionmentioning
confidence: 56%
“…Although there were no significant differences in survival curves and no major clinical signs in the different groups challenged with the Omicron BA.1 variant, viral load was also reduced in lungs from PHH-1V vaccinated animals compared to infected control animals. The reduction of infectivity and pathogenesis of the Omicron BA.1 variant in K18-hACE2 mice has been reported previously in various studies, including a study in which mRNA-1273 protective efficacy was evaluated against Omicron BA.1 (Tarrés-Freixas et al, 2022;Ying et al, 2022). Hence, PHH-1V vaccination can reduce and control infection of different VoCs, including Omicron BA.1, in lower respiratory airways.…”
Section: Discussionmentioning
confidence: 56%
“…The aromatic N501Y substitution that is present in the alpha, beta, and gamma VOC is associated with increased transmission in humans but also allows for infection in the wild-type mouse using the mouse ACE2 receptor [ 25 ]. Thus, 2 recent studies have shown that wild-type mice are susceptible to certain SARS-CoV-2 VOCs, specifically to the beta (B.1.351) and gamma (P1) VOCs [ 26 , 27 ], most likely due to the N501Y substitution. Although mild lesions and viral replication were observed in nasal turbinates and lung of these wild-type mice inoculated with these VOCs, no significant clinical signs were observed.…”
Section: Animal Models To Study Vocsmentioning
confidence: 99%
“…Conversely, studies in other models such as transgenic mice expressing the human ACE2 (huACE2) receptor driven by the cytokeratin-18 (K18) gene promoter (K18-huACE2) have yielded different outcomes. In these mice, infection with the beta VOC resulted in enhanced infectivity and a quicker disease progression in comparison to one of ancestral variants (B.1) [ 26 ]. Such enhanced infectivity could be due, at least to some extent, to the expression of higher levels of interferon antagonist proteins by some VOCs [ 33 ].…”
Section: Animal Models To Study Vocsmentioning
confidence: 99%
“…Amazingly, Q493R was found in mice-adapted SARS-CoV-2 lineage, but infection of mice with wild-type SARS-CoV-2 was not possible before Omicron. In this regard, VOC Beta( Ravi et al, 2021 ) and Gamma ( Montagutelli et al, 2021 ) could establish infection in wild-type mice, but with a milder infection than in human ACE2 transgenic mice ( Tarres-Freixas et al, 2021 ). Omicron, because of its ability to infect mice ( Bentley et al, 2021 , Liu et al, 2022 , Rissmann et al, 2022 , Suryawanshi et al, 2022 ), was hypothesized to emerge from partially fit jump species( Wei et al, 2021 ), and reversions after widespread circulation in humans could support such hypothesis.…”
Section: Co-infections and Recombinantsmentioning
confidence: 99%